(3GdeSdc GdSgd aj TQM JhTjM GHf Sgds - (3eMeO GdUZjQ Hf YHO Gddg GdhaQGfjs; (3GdMSf Hf YHO Gddg Hf Sgd Hf SYjO GHf jMji Hf egQGf GdnYrSncQj, CHh gdGd,J (B395 (3g` s ((3YHOGdSdGe Hf CMeO CRWhW s)
(3ChdgG (B:s
(3GdMeO ddg GdPj hVM LjO Cgd GdCOH HYbhO GdHjGf, GdJj gj Ydi GdTQa YfhGf s
(3BNQgG (B:s
(3hbGd eLjQ GdOjf GdESYQOj(B: (3YQVoJ cJGHj cj ojHGY HOQge Ydi eTJmQ YfO GdhaGA UMjM s
(3GHf Sgd gh(B: (3CHhESMGb EHQGgje Hf Sgd GdCTHjdj GdCfOdSj GdeJhai (B649(3g```s
(3ajg VHW bdjds
(3HgG fXGe GdJYbjHIs
(3HBNQgG CQLhRI aj hUa GdefGRd ddadcj GdeZQHj GdaGSj CHhYHOGddg Hf eMeO GdRehQj GdeJhai (B997(3g``` s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
Keywords: (3GdCOHs